Research on Quality Markers of Guizhi Fuling Prescription for Endometriosis Treatment Based on Gray Correlation Analysis Strategy - Chen, Jinpeng; Gai, Xiaohong; Xu, Xu; Liu, Yi; Ren, Tao; Liu, Suxiang; Ma, Ting; Tian, Chengwang; Liu, Changxiao (Frontiers in Pharmacology, 2021)
Guizhi Fuling prescription (GFP), a prestigious prescription of traditional Chinese medicine (TCM) which recorded in “Jingui Yaolue”, was composed of five herbs: Cinnamomi Ramulus, Poria Cosos, Moutan Cortex, Persicae Semen and Paeoniate Radix. It was efficiently used for the treament of endometriosis, primary dysmenorrhea and blood stasis for centuries. However, its Q-Markers of treating endometriosis has not been clearly elucidiated. In this study, a rapid method was established for Q-Markers investigation on GFP. A total of 50 potentially bioactive constituents including phenolic acids, paeoniflorin and its derivatives, triterpenoids and other species were identified based on the accurately measured mass value, fragmentation pattern and retention time by means of ultra performance liquid chromatography/quadrupole time-of-flight tandem mass spectrometry (UPLC/Q-TOF-MS/MS). Furthermore, regularity of recipe composition and grey correlaion analysis revealed that all of the characteristic peaks contributed to the treament of endometriosis. The relative correlation degrees were greater than 0.6. Among them, peak 1 and 10 which were most closely correlated to the endometriosis, were identified as amygdalin and cinnamic acid. Finally, all of the active ingredients were molecularly docked with proteins associated with endometriosis by Schrodinger. Among them, amygdalin, cinnamic acid, paeonol, gallic acid and paeoniflorin had the lower binding energies. It was proposed that these constituents could be directed at Q-Markers for GFP. Thus, the intergrated approach describing for revealing Q-Markers of GFP could be expected to provide a means for quality evaluation.